New Modular Multidimensional Digital Filter Structures - Rameshwaran, K.; Eswaran, C. (2005)
New multidimensional digital structures that use the concept of a generalized immittance converter are presented in this paper. The proposed filter structures are regular and modular, and they realize multiple transfer functions simultaneously; hence, they are attractive for very large-scale integration implementation. It is shown that these filter structures can be obtained by using a few specific digital modules as building blocks. The arrangements of the modules and the values of the multiplier constants that are used in these modules can be obtained directly from the specified discrete transfer function by using a computer program.